Case Report: Long-Term Survival of a Dog With Chronic Lymphocytic Leukemia Treated With Chlorambucil, Prednisolone, and Imatinib - Lee, Ga-Won; Kang, Min-Hee; Jeon, Jin-Ha; Song, Doo-Won; Ro, Woong-Bin; Kim, Heyong-Seok; Park, Hee-Myung (Frontiers in Veterinary Science, 2022)
A 7-year-old castrated male Poodle dog presented with chronic progressive lymphocytosis. Hematologic and peripheral blood smear findings included remarkable lymphocytosis with well-differentiated small lymphocytes. Cytology of bone marrow aspirate showed hypercellular integrity with infiltration of small mature lymphocytes, accounting for 45% of all nucleated cells. Flow cytometry of blood and marrow samples revealed neoplastic lymphocytes predominantly expressing the CD21 molecule. B-cell chronic lymphocytic leukemia (CLL) was diagnosed on an immunophenotypic analysis. Administrations of prednisolone and chlorambucil were initiated and the response was unremarkable. Therefore, additional treatment with imatinib was provided, which resolved the hematologic abnormalities associated with CLL. Flow cytometry after approximately 1 year of treatment showed normalization of the count of lymphocytes positive for CD21 and resolved hematologic lymphocytosis. The dog was followed-up for 2 years, and there were no severe adverse effects. This case indicates that imatinib may be a good option as an adjunctive therapy with prednisolone and chlorambucil treatment for CLL in dogs without treatment response.